Desarrollo de habilidades comunicativas con el uso de la herramienta pictoboard en niños con síndrome de down, trastorno del espectro autista (TEA) y discapacidad intelectual en un centro de educación básica especial - Huapaya Coronado, Maritza Del Pilar (2024)
La Victoria, located in the central area of ​​Lima, is a historic and traditional district, with a very rich culture and diversity, but with quite complex social problems that detract from its value. La Victoria Community and Cultural Center was born as a response to these problems and needs of the community, with the main objective of promoting social identity and the sense of belonging. The project is fully justified in all its aspects and levels, showing coherence with the context where it is located, with the people it serves and the needs it seeks to satisfy, providing an architecture rooted in the geographical and cultural context. During the development of this project, I got to know and connect with this place and its inhabitants, proposing a project of and for the community, with an important symbolic value that express the history and culture of the district of La Victoria, as well as coherence with my commitment and vision as an architect, "beauty must be justified to be really beautiful".